KCNV2 retinopathy: clinical features, molecular genetics and directions for future therapy. (3rd May 2020) - Guimaraes, Thales A. C. De; Georgiou, Michalis; Robson, Anthony G.; Michaelides, Michel
ABSTRACT: KCNV2: -associated retinopathy or "cone dystrophy with supernormal rod responses" is an autosomal recessive cone-rod dystrophy with pathognomonic ERG findings. This gene encodes Kv8.2, a voltage-gated potassium channel subunit that acts as a modulator by shifting the activation range of the K + channels in photoreceptor inner segments. Currently, no treatment is available for the condition. However, there is a lack of prospective long-term data in large molecularly confirmed cohorts, which is a prerequisite for accurate patient counselling/prognostication, to identify an optimal window for intervention and outcome measures, and ultimately to design future therapy trials. Herein we provide a detailed review of the clinical features, retinal imaging, electrophysiology and psychophysical studies, molecular genetics, and briefly discuss future prospects for therapy trials.